Armchair Sciurologist? Review of Peter Coates, Squirrel Nation: Reds, Greys and the Meaning of Home - Krauss, Judith (Humanimalia, 2024)
Review of:Peter Coates, Squirrel Nation: Reds, Greys and the Meaning of Home. London: Reaktion Books, 2023. 336 pp. 36 illus., 10 in colour. £16.99 (hb).